Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1093/0195169271.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and the Ecology of Poverty

Abstract: This book examines the HIV/AIDS epidemic in the social and economic context of poverty and economic crisis in developing and transition countries. It challenges the assumption — implicit in AIDS policy — that differences in sexual behavior are adequate to explain differences in HIV prevalence between populations. Using an epidemiological approach, the book shows how people who are malnourished, burdened with parasites and infectious diseases, and who lack access to medical care are more vulnerable to all disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 203 publications
0
32
0
3
Order By: Relevance
“…drug abuse, they might have concluded that the infection is neither a priority nor a threat to public health [9] . Political leaders, authorities, economists, members of the society and HIV affected people must join efforts to face AIDS epidemic [10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…drug abuse, they might have concluded that the infection is neither a priority nor a threat to public health [9] . Political leaders, authorities, economists, members of the society and HIV affected people must join efforts to face AIDS epidemic [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, authorities will generally reach their aims in matters of fairness more effectively if when focusing their help they take not only poverty indicators into account but also the presence of AIDS in the homes [10] . It is essential that available resources reach the homes of the neediest people through the combination of poverty reduction programs and measures mitigating the impact of HIV/AIDS epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Third, that it is the practice of concurrent sexual partnerships, which is claimed to be more common in southern Africa than in other parts of the world, that explains the difference. The scientific evidence has resolutely rejected the first two of these possible explanations (UNAIDS 1999;Gray et al 2001;Stillwaggon 2006). However, the third, the 'concurrency theory' has gained widespread acceptance and requires closer attention.…”
Section: Was There Really An Explanatory Gap In the Case Of Aids?mentioning
confidence: 99%
“…Individuals who already have diminished immune function-due to malnutrition, concurrent exposure to other infections, etc. -spend more time at higher viral loads, thus making them more infectious for more of the time (Stillwaggon 2006).…”
Section: Was There Really An Explanatory Gap In the Case Of Aids?mentioning
confidence: 99%